THE INDEXING APPROACH IN MEASURING OF SUSTAINABLE SOCIETY - Sarić, Radojica; Jeločnik, Marko; Popović, Vesna (Economics of Agriculture, 2013)
Sustainable society is a society that has ability to maintain a balance between economic, social and ecological processes, or states, over the time period, in order to meet, as current as well as future needs of the population. This is a complex and multidisciplinary concept, which requires establishment of appropriate indexes for measuring of a society sustainability level. Sustainable Society Index (SSI) is considered as one of the most recognized indexes for measuring the sustainability level of a society. In the paper is presented the model of Sustainable Society Index by defining its basic characteristics and trends, parallelly with quantitative-comparative analysis of the SSI value at the global level as well as at the level of the Republic of Serbia and neighboring countries.